Semitransparent organic solar cell based on spraying-spin coating combined technology
Through the spray-spin coating combined process, the contradiction between transparency and efficiency of semi-transparent organic solar cells is solved, and efficient and uniform film preparation is achieved, which reduces costs and expands the application range.
Patent Information
- Application Number
- CN202411664860.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
AI Technical Summary
While ensuring transparency, existing semi-transparent organic solar cells are difficult to improve device efficiency, and the preparation process is complex, high cost and poor film uniformity.
The photoactive layer is prepared by a spray-spin coating combination process. By adjusting the spray and spin coating parameters, the transmittance and interpenetration network structure of the active layer are optimized, and the exciton dissociation efficiency and carrier transmission rate are improved.
It significantly improves the uniformity and photoelectric properties of the film, reduces production costs, is suitable for translucent application scenarios, and broadens the applicable materials and equipment types.
Smart Images

Figure CN119486456A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic photovoltaic devices or organic semiconductor thin-film solar cells, and in particular relates to a semi-transparent organic solar cell based on a spray-spin coating combined process. Background Art
[0002] The application of semi-transparent organic solar cells in building integration is one of its most important applications. By integrating semi-transparent organic solar cells into windows, exterior walls, roofs and other parts of buildings, the self-sufficiency of buildings and energy conservation and emission reduction can be achieved. At the same time, this integrated building can also improve the aesthetics and comfort of the building, creating a more intelligent and environmentally friendly living space for people. Due to the characteristics of lightness and flexibility of semi-transparent organic solar cells, they can be used in portable devices such as mobile phones, tablets and laptops. By integrating semi-transparent organic solar cells on the surface of the device, the self-sufficiency and continuous charging of the device can be achieved, thereby extending the use time of the device.
[0003] Although some progress has been made in the research of semi-transparent organic solar cells, there are still many problems to be solved. In the future, researchers need to further explore new organic materials and device structures to improve the photoelectric conversion efficiency and stability of semi-transparent organic solar cells. At the same time, it is also necessary to further develop solutions combined with other solar energy utilization technologies to achieve the combined utilization of multiple energy sources. In addition, it is also necessary to strengthen the application research of semi-transparent organic solar cells in aspects such as building integration to promote their application in green buildings and sustainable development.
[0004] Semi-transparent organic solar cells require high light transmittance, so the thickness of the photoactive layer is limited, usually around 60nm. However, this also reduces the light absorption efficiency of the photoactive layer, which ultimately leads to a decrease in device performance. Therefore, how to find a suitable method to improve the device efficiency while ensuring the semi-transparency of solar cells is a key research direction. Summary of the invention
[0005] The problem to be solved by the present invention is: how to provide a semi-transparent organic solar cell based on a spray-spin coating combination process and a preparation method thereof, the purpose of which is to prepare a photoactive layer by introducing a spray-spin coating combination process to achieve: (1) by combining spin coating and spray coating processes, the problem of donor-acceptor agglomeration in the spray solution droplets is improved, and the transmittance of the photoactive layer is enhanced; (2) by regulating the spraying and spin coating parameters, the interpenetrating network of the donor-acceptor materials in the active layer is optimized, the donor-acceptor contact area is increased, and the exciton dissociation efficiency is improved; (3) a smoother carrier transmission channel is formed in the active layer, and the carrier transmission rate is increased; (4) while optimizing the transmittance of the photoactive layer, the device performance of the semi-transparent organic solar cell is improved.
[0006] The technical solution of the present invention is:
[0007] A semi-transparent organic solar cell based on a spray-spin coating process is characterized in that the solar cell adopts an inverted structure, which comprises, from bottom to top, a substrate, a transparent conductive cathode ITO, a cathode buffer layer, a photoactive layer, an anode buffer layer, and a metal anode; the spray-spin coating process is characterized in that when a solution method is used to prepare the photoactive layer, the substrate is first placed on a spin coater and rotated at a fixed rate, and then a spraying device is used to evenly spray the photoactive layer solution on the rotating substrate to finally prepare a photoactive layer film.
[0008] Preferably, in the spray-spin coating combined process, the parameters of the spin coater are set to 2000-5000rpm / min, and the spin coating time is 30-50s; the spray flow rate of the spray equipment is 50-200ul / min, and the height from the substrate on the spin coater is 10-20cm. The spraying time is controlled according to the final film thickness, and the active layer film thickness is between 30-60nm.
[0009] Preferably, the solution of the photoactive layer is prepared from a mixed solution of an electron donor material PBDB-T and an electron acceptor material ITIC, and the solvent is selected from one of chlorobenzene, dichlorobenzene, toluene and xylene; the mass percentage of PBDB-T and ITIC in the mixed solution is between 1:3 and 3:1, and the concentration of the mixed solution is 10 to 30 mg / ml.
[0010] Preferably, the cathode buffer layer material is ZnO, TiO2, AZO, Al2O3, etc., and the thickness ranges from 10 to 20 nm.
[0011] Preferably, the anode buffer layer material is one of MoO3, NPB, TAPC, and HATCN, the thin layer thickness ranges from 5 to 10 nm, and is prepared by vacuum thermal evaporation.
[0012] Preferably, the metal cathode material is one of Ag, Al or Au, the thin layer thickness ranges from 20 to 40 nm, and is prepared by vacuum thermal evaporation.
[0013] Preferably, the substrate material is glass or a transparent polymer, and the transparent polymer material is one or more of polyethylene, polymethyl methacrylate, polycarbonate, polyurethane, polyimide, chloroacetic acid resin or polyacrylic acid.
[0014] Preferably, the preparation process comprises the following steps:
[0015] 1) Cleaning the substrate composed of the transparent substrate and the transparent conductive cathode ITO, and drying it with nitrogen after cleaning;
[0016] 2) spin coating, printing or spraying a cathode buffer layer on the surface of the transparent conductive cathode ITO, and performing thermal annealing;
[0017] 3) preparing a PBDB-T:ITIC photoactive layer on the cathode buffer layer by a spray-spin coating process, and then performing a thermal annealing treatment on the obtained photoactive layer;
[0018] 4) sending the substrate with the active layer into a vacuum evaporation device to prepare an anode buffer layer on the photoactive layer;
[0019] 5) Evaporate a metal cathode on the anode buffer layer.
[0020] Preferably, the cathode buffer layer thermal annealing temperature in step (2) is in the range of 150-300°C, and the time range is 30-90 min. The photoactive layer annealing temperature in step (3) is in the range of 50-80°C, and the time range is 20-40 min. The thermal annealing method adopts one or more of constant temperature hot plate heating, oven heating, far infrared heating, and hot air heating.
[0021] The advantages and significant technical advances of the present invention are:
[0022] First, by using a combined spray-spin coating process, the aggregation behavior of droplets on the substrate during the spray coating process is significantly improved. While the droplets are evenly spread on the substrate surface, the high-speed spin coating of the substrate accelerates the film formation process of the droplets. Under the synergistic effect of centripetal force and droplet tension, the agglomeration of donor and acceptor materials in the droplets is reduced, thereby improving the transmittance of the prepared active layer film.
[0023] By adjusting the spraying and spin coating process parameters, a more suitable interpenetrating network structure is formed between the donor and the acceptor in the active layer, the contact area of the donor and the acceptor materials is increased, and the dissociation efficiency of the excitons at the donor and the acceptor interface is made higher.
[0024] The spray-spin coating process combines the uniformity of spray coating and the adhesion of spin coating, regulates the morphology of the active layer film, improves the crystallization characteristics of the donor and acceptor materials, and thus improves the carrier mobility.
[0025] The combined spray-spin coating process not only optimizes the transmittance of the photoactive layer, but also improves the carrier dynamics in the active layer, thereby obtaining high-performance semi-transparent organic solar cells.
[0026] Second, the technical solution of the present invention mainly solves the problems of poor film uniformity and transparency, high preparation cost and complex process in the traditional solar cell preparation method in industrial application, which is specifically manifested in the following aspects and brings significant technological progress:
[0027] 1. Improve the uniformity and performance consistency of the film
[0028] Traditional solar cell thin film preparation mostly uses a single spin coating or spray coating process. The spin coating process causes the film to be thicker at the edges and thinner in the center, while the spray coating process causes uneven local thickness of the film, affecting the uniformity of the photoactive layer and the consistency of the optoelectronic performance.
[0029] The present invention combines spraying and spin coating processes to allow the photoactive layer solution to be evenly sprayed during the rotation of the substrate, thereby significantly improving the uniformity of the film. The spray-spin coating process can ensure the uniformity of the overall film and the consistency of electrical properties while maintaining good film thickness control, thereby improving the overall performance of the solar cell.
[0030] 2. Improve the light transmittance of solar cells, suitable for semi-transparent applications
[0031] Most traditional organic solar cells are opaque, which limits their use in semi-transparent applications such as architectural glass and smart windows. In addition, traditional methods make it difficult to achieve precise thickness control of the film, which affects the light transmittance of the cell.
[0032] Through the spray-spin coating process, the present invention can prepare a photoactive layer film with a thickness controlled between 30-60nm, which greatly improves the light transmittance of solar cells and makes them suitable for semi-transparent application scenarios. This technology achieves higher light transmittance without affecting power generation efficiency, meeting the needs of products such as architectural glass and smart windows.
[0033] 3. Simplify the process and reduce production costs
[0034] The preparation process of traditional organic solar cells is complicated, including multi-step coating, thermal annealing, vacuum evaporation, etc., which increases production cost and time.
[0035] The present invention can complete the coating of the photoactive layer through a one-time spray-spin coating process, which simplifies the preparation process, and the precise control of the spraying parameters optimizes the requirements for subsequent annealing temperature and time. This process not only shortens the preparation time, but also reduces material consumption, thereby reducing the overall production cost, making the technology more commercially viable.
[0036] 4. Applicable to a variety of substrate materials, broadening the scope of application
[0037] Some traditional processes are only applicable to rigid glass substrates, and there are technical difficulties in applying them on flexible substrates, which limits the expansion of solar cells in wearable devices, smart windows and architectural applications.
[0038] The spray-spin coating combined process of the present invention can be applied to transparent polymer substrates such as glass, polycarbonate, polyethylene, and polymethyl methacrylate, making the technology suitable not only for rigid devices but also for flexible devices. It broadens the application field of organic solar cells and can be applied to a variety of scenarios such as smart windows, wearable devices, and building materials.
[0039] The technical solution of the present invention not only solves the problems of poor film uniformity, insufficient light transmittance, complex process, high cost and other problems in the prior art, but also significantly improves the overall performance, applicability and economy of solar cells, and has important industrial application value. These advances provide technical support for the large-scale promotion of organic solar cells and their wide application in the fields of architecture, smart homes, wearable devices, etc.
[0040] Third, the technical parameters of the present invention:
[0041] 1) Preparation process of photoactive layer
[0042] Process type: Spray-spin coating combined process.
[0043] Spin coating parameters: Spin speed is 2000-5000 rpm / min, duration is 30-50 seconds.
[0044] Spraying parameters: spraying flow rate is 50-200μl / min, spraying distance is 10-20cm, and film thickness is 30-60nm.
[0045] Thermal annealing: After spraying, the film is annealed at 50-80°C for 20-40 minutes.
[0046] 2) Photoactive layer material parameters
[0047] Material composition: mixed solution of PBDB-T and ITIC.
[0048] Mixing ratio: The mass percentage of PBDB-T and ITIC is 1:3 to 3:1.
[0049] Solvent choices: chlorobenzene, dichlorobenzene, toluene or xylene.
[0050] Solution concentration: 10-30mg / ml.
[0051] 3) Buffer layer and electrode material parameters
[0052] Cathode buffer layer: one or more combinations of ZnO, TiO2, AZO, Al2O3, with a thickness of 10-20nm, prepared by spin coating, printing or spraying, and thermal annealing.
[0053] Anode buffer layer: one of MoO3, NPB, TAPC, and HATCN, with a thickness of 5-10 nm, prepared by vacuum thermal evaporation.
[0054] Metal anode: evaporated metal material.
[0055] Existing technical problems solved:
[0056] 1) Problems of uniformity and repeatability of film preparation
[0057] Existing problems: Traditional photoactive layer film preparation methods, such as single spin coating or spray coating, have problems with poor film uniformity and difficulty in thickness control, which affects the performance and stability of solar cells.
[0058] The solution of the present invention is to spray the photoactive layer solution simultaneously during the spin coating process through a combined spray-spin coating process, thereby achieving uniform film coverage and precise thickness control, and effectively improving film quality and repeatability.
[0059] 2) Low material utilization
[0060] Existing problem: Traditional spin coating method causes serious waste of materials, resulting in increased manufacturing costs.
[0061] The solution of the present invention: The spray-spin coating process significantly reduces material waste and improves the utilization rate of the photoactive material by accurately controlling the spray flow rate and the spray area.
[0062] 3) Insufficient optical and electrical properties of thin films
[0063] Current problem: The thin films prepared by existing processes have limited performance in light absorption and charge transport, which affects the efficiency of solar cells.
[0064] The solution of the present invention: combining the optimized ratio of PBDB-T and ITIC and thermal annealing treatment, the crystallinity and phase separation effect of the film are enhanced, and the light absorption and charge migration performance are improved.
[0065] 4) Difficulty in controlling the thickness of the photoactive layer
[0066] Current problem: The film thickness is difficult to control accurately, resulting in large fluctuations in device performance.
[0067] The solution of the present invention is to realize dynamic thickness control through a combined spray-spin coating process, so that the thickness of the photoactive layer is accurately within the range of 30-60nm, thereby ensuring the stability of the photoelectric performance of the device.
[0068] Significant technological advances achieved:
[0069] 1) Improved film uniformity
[0070] The combined spray-spin coating process achieves high uniformity of film thickness, reduces defect rate, and significantly improves the surface quality of the photoactive layer through the synergistic effect of spin coating and spray coating.
[0071] 2)Optimization of photoelectric performance
[0072] By using an optimized ratio of PBDB-T and ITIC (1:3 to 3:1) and appropriate thermal annealing conditions (50-80°C, 20-40 minutes), the light absorption capacity and charge mobility of the photoactive layer were significantly improved.
[0073] The optimized film has excellent optoelectronic properties, laying the foundation for improving the efficiency of solar cells.
[0074] 3) Improved material utilization
[0075] The combined spray-spin coating process effectively reduces material waste. Compared with the traditional spin coating process, the material utilization rate is increased by 20%-30%, which significantly reduces the production cost.
[0076] 4) Manufacturing process flexibility
[0077] The wide adjustability of spray and spin coating parameters (such as spray flow, spin coating speed and film thickness) makes the process suitable for different material systems and device requirements.
[0078] The process can be easily integrated with existing industrial equipment and has strong scalability and industrialization potential.
[0079] 5) Environmental friendliness
[0080] Environmentally friendly solvents such as chlorobenzene, dichlorobenzene, toluene or xylene are used to reduce the impact on the environment.
[0081] While reducing material waste, it also reduces waste generation.
[0082] The present invention successfully solves the key problems of film uniformity, thickness control, material utilization rate and so on in the prior art through the innovative spray-spin coating combined process, and realizes the significant optimization of the solar cell preparation process. It has significant technical progress in improving photoelectric performance, reducing manufacturing costs and enhancing process flexibility, and has broad application prospects and industrial value. BRIEF DESCRIPTION OF THE DRAWINGS
[0083] Figure 1 This is a schematic structural diagram of a semi-transparent organic solar cell based on a spray-spin coating combined process according to the present invention, from bottom to top: 1 represents a substrate; 2 represents a transparent conductive cathode ITO; 3 represents a cathode buffer layer; 4 represents a photoactive layer; 5 represents an anode buffer layer; and 6 represents a metal anode. DETAILED DESCRIPTION
[0084] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0085] The following are two specific industrial application examples based on the "spray-spin coating combined process":
[0086] Example 1: Organic solar cells for semi-transparent architectural glass
[0087] Application background: There is a high demand for translucent solar glass in the construction field, especially in the glass curtain walls of high-rise buildings, which can both provide lighting and generate electricity.
[0088] Implementation steps:
[0089] 1. Substrate selection and processing: Select transparent polymer or glass as the substrate, clean it and blow it dry with nitrogen.
[0090] 2. Spray-spin coating process: Place the substrate on a spin coater and spin at 3000 rpm. Use the spray equipment to spray the photoactive layer solution containing PBDB-T and ITIC (concentration of 20 mg / ml, chlorobenzene solvent) at a spray flow rate of 100 μl / min and a height of 15 cm from the substrate to form a uniform photoactive layer.
[0091] 3. Post-treatment of the film: The sprayed photoactive layer was placed on a constant temperature table at 60°C for thermal annealing for 30 minutes to improve its photoelectric performance.
[0092] 4. Electrode coating: A 5 nm thick MoO2 layer was deposited on the photoactive layer by vacuum thermal evaporation as an anode buffer layer, followed by a 40 nm thick silver layer as a metal anode.
[0093] When the semi-transparent organic solar cells prepared by this method are used on building glass curtain walls, they have moderate light transmittance, can ensure a certain lighting effect, and at the same time have stable solar power generation capabilities to provide clean energy for the building.
[0094] Example 2: Organic photovoltaic films for smart windows
[0095] Application background: Smart windows can generate electricity under light, which can be used to supply power or adjust the color and transmittance of windows. They are widely used in smart homes and automobiles.
[0096] Implementation steps:
[0097] 1. Substrate selection and processing: Flexible transparent polymers such as polyethylene or polycarbonate are selected as substrates so that the prepared photovoltaic film has a certain degree of flexibility and is suitable for smart window applications.
[0098] 2. Spray-spin coating process: Place the substrate on a spin coater and spin at 2500 rpm. Use a spray coating device to spray a mixed solution of PBDB-T and ITIC (ratio 1:1, concentration 15 mg / ml, toluene solvent) at a spray flow rate of 80 μl / min from a height of 12 cm from the substrate to form a photoactive layer film with a thickness of about 50 nm.
[0099] 3. Film post-treatment: After spraying, the photoactive layer film was placed in an oven at 70°C for thermal annealing for 20 minutes.
[0100] 4. Electrode coating: A layer of 8 nm TAPC was prepared on the photoactive layer as an anode buffer layer by vacuum evaporation, and then a 30 nm thick aluminum layer was evaporated as a metal anode.
[0101] The organic photovoltaic film prepared by this process has good light transmittance and flexibility, which is suitable for smart window applications. When sunlight shines, the film can generate electricity to provide electricity for windows to adjust light and color. At the same time, it has the advantages of low cost and high processing efficiency, which is suitable for large-scale production.
[0102] The general preparation process of all examples is as follows:
[0103] A substrate composed of a transparent substrate and a transparent conductive cathode ITO with a surface roughness less than 1 nm is cleaned and blown dry with nitrogen after cleaning; a ZnO solution is spin-coated on the surface of the transparent conductive cathode ITO (2000 rpm, 40 s, 20 nm) to prepare a cathode buffer layer, and the formed film is thermally annealed (150° C., 60 min); a PBDB-T:ITIC (1:1, 15 mg / ml) photoactive layer is prepared on the cathode buffer layer by using different spray-spin coating combined processes (the thickness of the photoactive layer in all embodiments is controlled to be 50 nm), and the formed active layer film is thermally annealed (60° C., 30 min); an anode buffer layer MoO3 (8 nm) and a metal anode Au (40 nm) are evaporated on the cathode buffer layer.
[0104] The spray-spin coating combined process and the corresponding device performance corresponding to each embodiment are shown in the following table:
[0105] Table 1 Semi-transparent organic solar cell device performance parameters
[0106]
[0107] It can be seen from the above table that by optimizing the parameters of spraying and spin coating in the spray-spin coating combined process, the photovoltaic efficiency and transmittance of the optimized device are improved compared with the control device using pure spin coating and spray coating, and Example 5 is the most obvious device performance improvement among all the examples. It can be seen that the spray-spin coating process effectively regulates the donor-acceptor agglomeration phenomenon in the film formation process of the active layer, and while improving the light transmittance of its thin film, the improvement of the donor-acceptor interpenetrating network also improves the exciton dissociation efficiency and carrier mobility of the device, and finally obtains a semi-transparent organic solar cell with high photovoltaic efficiency.
[0108] The following are 6 specific embodiments based on the above preferred conditions:
[0109] Example 1: Semi-transparent organic solar cells for smart windows
[0110] Photoactive layer: a mixed solution of PBDB-T and ITIC, with a mass percentage of 1:1 and a concentration of 20 mg / ml, and the solvent is chlorobenzene.
[0111] Cathode buffer layer: ZnO, thickness 15 nm.
[0112] Anode buffer layer: MoO3, thickness 7nm, prepared by vacuum thermal evaporation method.
[0113] Metal cathode: Ag, thickness 30 nm, prepared by vacuum thermal evaporation.
[0114] Substrate material: Polycarbonate, providing good flexibility and transparency.
[0115] Application scenarios: Suitable for smart windows, which can generate electricity under sunlight and provide power for adjusting the color and transmittance of windows.
[0116] Example 2: Semi-transparent solar cells for building glass curtain walls
[0117] Photoactive layer: a mixed solution of PBDB-T and ITIC, with a mass percentage of 1:3 and a concentration of 15 mg / ml, and the solvent is dichlorobenzene.
[0118] Cathode buffer layer: TiO2, thickness 10nm.
[0119] Anode buffer layer: NPB, thickness 5 nm, prepared by vacuum thermal evaporation.
[0120] Metal cathode: Al, thickness 35 nm, prepared by vacuum thermal evaporation.
[0121] Substrate material: Glass, suitable for architectural glass applications.
[0122] Application scenario: It integrates power generation and lighting functions and is used in glass curtain walls of high-rise buildings to provide auxiliary power.
[0123] Example 3: Flexible solar cells for wearable devices
[0124] Photoactive layer: a mixed solution of PBDB-T and ITIC, with a mass percentage of 3:1 and a concentration of 25 mg / ml, and the solvent is toluene.
[0125] Cathode buffer layer: AZO, thickness 12 nm.
[0126] Anode buffer layer: TAPC, thickness 6nm, prepared by vacuum thermal evaporation method.
[0127] Metal cathode: Au, thickness 20 nm, prepared by vacuum thermal evaporation.
[0128] Substrate material: Polyimide, highly flexible and durable.
[0129] Application scenarios: Applied to wearable devices such as smart bracelets and smart clothing to provide clean energy.
[0130] Example 4: Semi-transparent photovoltaic film for automotive windows
[0131] Photoactive layer: a mixed solution of PBDB-T and ITIC, with a mass percentage of 2:1 and a concentration of 18 mg / ml, and the solvent is xylene.
[0132] Cathode buffer layer: Al2O3, thickness 20nm.
[0133] Anode buffer layer: HATCN, thickness 8 nm, prepared by vacuum thermal evaporation.
[0134] Metal cathode: Ag, thickness 40 nm, prepared by vacuum thermal evaporation.
[0135] Substrate material: Polymethyl methacrylate (PMMA), providing excellent transparency.
[0136] Application scenarios: Suitable for car side windows and sunroofs, providing sunshade function and generating electricity for in-car equipment.
[0137] Example 5: Organic solar cells for greenhouses
[0138] Photoactive layer: a mixed solution of PBDB-T and ITIC, with a mass percentage of 1:1 and a concentration of 10 mg / ml, and the solvent is chlorobenzene.
[0139] Cathode buffer layer: ZnO, thickness 10 nm.
[0140] Anode buffer layer: MoO3, thickness 5nm, prepared by vacuum thermal evaporation method.
[0141] Metal cathode: Al, thickness 25 nm, prepared by vacuum thermal evaporation.
[0142] Substrate material: Transparent polyethylene, flexible and highly transparent.
[0143] Application scenarios: It can be used in greenhouses to provide suitable light for plant growth and generate electricity for use in the greenhouse system.
[0144] Example 6: Flexible photovoltaic film for electronic device screens
[0145] Photoactive layer: a mixed solution of PBDB-T and ITIC, with a mass percentage of 3:1 and a concentration of 30 mg / ml, and the solvent is dichlorobenzene.
[0146] Cathode buffer layer: TiO2, thickness is 15nm.
[0147] Anode buffer layer: TAPC, thickness 7nm, prepared by vacuum thermal evaporation method.
[0148] Metal cathode: Au, thickness 25 nm, prepared by vacuum thermal evaporation.
[0149] Substrate material: Polyacrylic acid, both flexible and transparent.
[0150] Application scenarios: Suitable for flexible screens of electronic devices such as mobile phones and tablets, using photovoltaic films to provide backup power for the devices.
[0151] These embodiments demonstrate the wide application of the spray-spin coating combined process in different industries and embody the optimized configuration of various process parameters in different application scenarios.
[0152] The present invention has been described by the above embodiments, but it should be understood that the above embodiments are only for the purpose of example and description, and are not intended to limit the present invention to the scope of the described embodiments. In addition, it can be understood by those skilled in the art that the present invention is not limited to the above embodiments, and more variations and modifications can be made according to the teachings of the present invention, and these variations and modifications all fall within the scope of the protection claimed by the present invention. The protection scope of the present invention is defined by the attached claims and their equivalents.
Claims
1. A semi-transparent organic solar cell based on a spray-spin coating process, characterized in that: The solar cell adopts an inverted or positive structure, and includes, from bottom to top, a transparent substrate, a transparent conductive cathode ITO, a cathode buffer layer, a photoactive layer, an anode buffer layer and a metal anode; or a transparent substrate, a transparent conductive anode ITO, an anode buffer layer, a photoactive layer, a cathode buffer layer and a metal cathode.
2. The solar cell according to claim 1, characterized in that: The photoactive layer is prepared by a combined spray-spin coating process, which specifically includes the following steps: placing a substrate on a spin coater and rotating it at a fixed speed, and using a spray coating device to evenly spray the photoactive layer solution on the surface of the rotating substrate to form a thin film.
3. The solar cell according to claim 2, characterized in that: The cathode buffer layer material is one or more combinations of ZnO, TiO2, AZO, and Al2O3, and the thickness of the thin layer ranges from 10 to 20 nm.
4. The solar cell according to claim 3, characterized in that: The anode buffer layer material is one of MoO3, NPB, TAPC and HATCN, the thickness of the thin layer is in the range of 5-10 nm, and is prepared by vacuum thermal evaporation.
5. The solar cell according to claim 4, characterized in that: The photoactive layer is prepared from a mixed solution of PBDB-T and ITIC, and the mass percentage of PBDB-T to ITIC is between 1:3 and 3:
1. The solvent is selected from one of chlorobenzene, dichlorobenzene, toluene or xylene.
6. The solar cell according to claim 5, characterized in that: The preparation process of the solar cell includes the following steps: 1) Clean the substrate and blow dry it with nitrogen; 2) spin coating, printing or spraying a cathode buffer layer on the surface of the transparent conductive cathode ITO and performing thermal annealing; 3) preparing the PBDB-T:ITIC photoactive layer by a spray-spin coating process and thermally annealing the layer; 4) sending the substrate into a vacuum evaporation device to prepare an anode buffer layer; 5) Finally, a metal anode is evaporated on the anode buffer layer.
7. A spray-spin coating combined process, characterized in that: The process is used to prepare a photoactive layer film, and comprises the following steps: a) fixing the substrate on a spin coater and rotating it at a speed of 2000-5000 rpm / min; b) using a spraying device with a spraying flow rate of 50-200 μl / min, spraying the photoactive layer solution uniformly at a height of 10-20 cm from the substrate.
8. The spray-spin coating combined process according to claim 7, characterized in that: The photoactive layer solution includes a mixed solution of PBDB-T and ITIC, the solvent is selected from one of chlorobenzene, dichlorobenzene, toluene or xylene, the mass percentage of PBDB-T and ITIC is 1:3 to 3:1, and the concentration of the mixed solution is 10-30 mg / ml.
9. The spray-spin coating combined process according to claim 7, characterized in that: The duration of spin coating in the process is 30-50 seconds, and the spray coating time is controlled according to the required film thickness, so that the thickness of the prepared photoactive layer film is between 30-60 nm.
10. The spray-spin coating combined process according to claim 7, characterized in that: During the spray-spin coating process, the sprayed photoactive layer film is thermally annealed at a temperature of 50-80° C. for 20-40 minutes to enhance the optical and electrical properties of the film.